Performativitet Teoretiska tillämpningar i konstvetenskap : 1 - Snickare, Mårten; Hedlin Hayden, Malin (Stockholm Studies in Culture and Aesthetics, 2017)
"What does performativity signify? And what does it mean to speak of something as being performative? Aiming to clarify and critically highlight an important but sometimes elusive concept, this book consists of five chapters, each addressing a concrete situation of interpretation. By highlighting artworks and images from different historical periods and contexts, the authors show how performativity might be a versatile and useful concept for interpretations of images. The purpose is to convey the critical potential of the concept as it is activated in relation to different objects of study. The book is primarily addressed to students of art history and others who take an interest in questions of visuality and visual practices. Offering not only a theoretical understanding of the concept, it strives to point out ways and possibilities of the practical use of performativity. This book constitutes the first volume of Theoretical Applications in Art History, which forms part of the series Basic Readings in Culture and Aesthetics. Its editors, Malin Hedlin Hayden and Mårten Snickare, are professors of art history at the Department of Culture and Aesthetics, Stockholm University. ***